Mapping of occupational health and safety management indicators in the construction processes of the works of educational centers - Tovar Arredondo, Freddy (2022)
This research seeks to establish one of the methodologies for the establishment of a series of management indicators in construction projects in educational centers, in order to improve performance in monitoring the management of health and safety at work and thus reduce the level of accident rates in high-risk works of the works. The method used to develop a mapping of indicators consisted of identifying the stages of the construction processes of the work of an educational center, followed by the selection of the performance indicators of safety and health at work, according to a series of established criteria such as hazard identification, risk assessment and control measures and legal requirements such as Supreme Decree No. 011-2019-TR. Health and Safety Regulations at Work for the Construction Sector. The research argues that a mapping of well-identified reactive and proactive indicators in the construction processes of a project of a work in an educational center, led to effective monitoring in the measurement of the objectives and goals in the management of health and safety in the job.